Silent Free Fall at Disease Onset: A Perspective on Therapeutics for Progressive Multiple Sclerosis - LoPresti, Patrizia (Frontiers in Neurology, 2018)
Central nervous system (CNS) degeneration occurs during multiple sclerosis (MS) following several years of reversible autoimmune demyelination. Progressive CNS degeneration appears later during the course of relapsing-remitting MS (RRMS), although it starts insidiously at disease onset. We propose that there is an early subclinical phase also for primary-progressive (PP) MS. Consensus exists that many different cell types are involved during disease onset. Furthermore, the response to the initial damage, which is specific for each individual, would result in distinct pathological pathways that add complexity to the disease and the mechanisms underlying progressive CNS degeneration. Progressive MS is classified as either active or not active, as well as with or without progression. Different forms of progressive MS might reflect distinct or overlapping pathogenetic pathways. Disease mechanisms should be determined for each patient at diagnosis and the time of treatment. Until individualized and time-sensitive treatments that specifically target the molecular mechanisms of the progressive aspect of the disease are identified, combined therapies directed at anti-inflammation, regeneration, and neuroprotection are the most effective for preventing MS progression. This review presents selected therapeutics in support of the overall idea of a multidimensional therapy applied early in the disease. This approach could limit damage and increase CNS repair. By targeting several cellular populations (i.e., microglia, astrocytes, neurons, oligodendrocytes, and lymphocytes) and multiple pathological processes (e.g., inflammation, demyelination, synaptopathy, and excitatory/inhibitory imbalance) progressive MS could be attenuated. Early timing for such multidimensional therapy is proposed as the prerequisite for effectively halting progressive MS.